Adsorption of boron using modified multiwalled carbon nanotubes - Zohdi, Nima (2013)
Boron is mostly used in the form of boric acid and borates in various industries.However, due to its toxicity to animals and plants, discharge of boron contained waste must be controlled at sustainable and safe level. In order to remove boron from the water to a desirable level to meet the requirement set by the legislation, multi walled carbon nanotubes (MWCNT) was used and modified by using three different chemicals which are glucose, sorbitol and tartaric acid. Surface chemistry of modified-MWCNT (m-MWCNT) was studied through Boehm technique to evaluate the quantity of oxygen containing functional groups. The results showed that tartaric acid m-MWCNT contained the highest amount of oxygen containing functional groups. Also,Fourier Transform Infrared Spectroscopy (FTIR) confirmed that carboxylic groups were formed on the surface of the m-MWCNT. Brunire Emmett Teller (BET) results showed no significant increase in surface area after modification of MWCNTs with these three organic chemicals comparing to the unmodified-MWCNTs. Boron adsorption characteristic of m-MWCNT samples was investigated under different pH, dosage of m-MWCNT, initial boron concentration, contact time and temperature. The tartaric acid m-MWCNT adsorbed the maximum amount of 1.97 mg/g of boron from contaminated water at pH of 6, temperature of 25 C, contact time of 60 min and dosage adsorbent of 0.4 g/l. At the same condition glucose m-MWCNT and sorbitol m-MWCNT adsorbed around 1.53 and 1.14 mg/g of boron respectively. The isotherm study of the adsorption revealed that adsorption behavior was best described by Freundlich model for all three modified samples. Lagergren-first-order, Pseudo-second-order and Intraparticle diffusion models were applied to determine the kinetics of the adsorption process. Pseudo-second order results showed higher coefficient of determination (R2) values for all three modifications comparing to the Lagergren-first-order. Sample with the highest adsorption capacity from the adsorption experiments was MWCNT modified with tartaric acid. It was selected for solid-liquid separation study where it was impregnated with magnetic property. Magnetized m-MWCNT was characterized by using FTIR, X-ray differactometer (XRD), SEM and EDX. The change in boron adsorption behavior of magnetized tartaric acid m- MWCNTs was also studied. Boron adsorption capacity of m-MWCNTs decreased very slightly from 1.97 mg/g to 1.91 mg/g. Separation of used m-MWCNT was carried out successfully by using a simple magnet. The quantitative analysis showed that only 0.03% of magnetized MWCNT was not adsorbed by the magnet.